Passengers' Perceptions Towards Air-Conditioned Buses in Nepal - Nepal, Pramshu (Kaladarpan कलादर्पण, 2023)
In order to promote social and environmental causes, bus services are extremely important. In order to raise productivity, promote economic growth, and improve access to mar- kets and services, transportation infrastructure and services should be expanded. This includes the creation of air-conditioned buses. The objective of the study is to understand how passengers feel about traveling in air-conditioned buses in Nepal. The descriptive type of research methodology was used to conduct the study. Reliability, responsibility, empathy, tangibility, and assurance are the five aspects used to evaluate a company's performance in providing services. Majority of respondents were dissatisfied with bus crew's ability to provide accurate bus arrival times and an- swer questions. 83.33 % of respondents replied that chairs of buses are comfortable to sit on. Re-garding safe traveling and trustworthiness many of the respondents are satisfied with the bus staff.